Bishops Who Live Like Princes: Bishop Tebartz-van Elst and the Challenge of Defining Corruption. (2nd January 2018) - Albisu Ardigó, Iñaki; Hough, Dan
Abstract : This article contributes to the debate on defining corruption. Rather than attempting to provide a definitive definition, it uses the case of Franz-Peter Tebartz-van Elst, a German bishop from the diocese of Limburg who stepped down in 2014, to illustrate that the disciplines of law, political science, economics, and anthropology all make important contributions to understanding what corruption is and how it should be conceptualized. Seen through these different lenses, the article argues, the case of "Bishop Bling" can be understood in strikingly different ways. This has ramifications not just for the case itself but also for how analysts understand corruption more broadly. Adopting an overtly interdisciplinary approach does not represent a way to "solve" the definitional dilemma, but it can help analysts understand more about corruption's multiplicity.